2010
DOI: 10.3390/su2040890
|View full text |Cite
|
Sign up to set email alerts
|

Radioactivity in Oily Sludge and Produced Waste Water from Oil: Environmental Concerns and Potential Remedial Measures

Abstract: Produced water separated from oil is usually returned to the environment and could permeate through the water table. If such water is contaminated with radioactive substances, it could create a definite threat to the water supply, especially in arid regions where ground water and overhead streams are sources of potable water. Low-level radioactive contamination of oily sludge is equally hazardous and also leads to detrimental pollution of water resources. We investigated the distribution of 226Ra, 40K and 228A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…232,[245][246][247][248] Impact on surface water. 8,138,225,249 All effluents from the oil and gas industry such as produced water, washing water for rigs, drilling machines, maintenance and repair, oil grease contaminated water, liquid sludge, etc., may contain radioactive materials. Consequently, discharging into the environment and lead to the release of these materials into the surface of the earth and may cause unexpected damage due to increase the concentrations of radioactive materials by leakage to subsurface water.…”
Section: The Main Forms Of Petroleum Pollution Tenormsmentioning
confidence: 99%
See 1 more Smart Citation
“…232,[245][246][247][248] Impact on surface water. 8,138,225,249 All effluents from the oil and gas industry such as produced water, washing water for rigs, drilling machines, maintenance and repair, oil grease contaminated water, liquid sludge, etc., may contain radioactive materials. Consequently, discharging into the environment and lead to the release of these materials into the surface of the earth and may cause unexpected damage due to increase the concentrations of radioactive materials by leakage to subsurface water.…”
Section: The Main Forms Of Petroleum Pollution Tenormsmentioning
confidence: 99%
“…Therefore, the external radiation dose and associated risks in the vicinity of oil and gas facilities increases as sludge builds up. 138,191 Sludge may be classied as hazardous wastes (more than the solid wastes) because it is oen in liquid form, so when disposed of, it always seeps through the soil and gradually pollutes groundwater and shallow groundwater.…”
mentioning
confidence: 99%
“…Oman tested the treatment and use of oil-containing wastewater for irrigation as an alternative to injecting the water back into aquifers, contaminating groundwater resources (JPEC, 1999). The de-oiling of produced water was also researched by Sultan Qaboos University in Oman (Pillay et al, 2010), which found that constructed wetlands could also be used to dispose of the treated produced water.…”
Section: Produced Water Use By the Oil Industrymentioning
confidence: 99%